EFFECT OF ADMINISTRATOR’S ROLE IN TRAINING PROGRAMS ON TRAINEES’ MOTIVATION - Ismail, Azman; Ab. Hamid, Siti Ngayesah; Ahmad, Nor Anis Nadira; Abdullah, Nor’ Ain; Yeop Yunus, Nek Kamal (Management Research Journal, 2015)
This study investigates the association between administrator’s role in training programs and trainees’ motivation. A survey method was utilized to gather self-report questionnaires from employees at a largest banking group of employees in Malaysia. The SmartPLS was employed to test the research hypotheses and outcomes of this test displayed two important findings: firstly, support was insignificantly related to trainees’ motivation. Secondly, assignment was significantly related to trainees’ motivation. This finding confirms that support does not act as a significant antecedent of trainees’ motivation, but assignment does act as a significant determinant of trainees’ motivation in the organizational sample. Further, discussion, implications and conclusion are elaborated.